Gormony zhirovoy tkani i funktsional'nayaaktivnost' shchitovidnoy zhelezy (Ожирение и метаболизм, 2010)
The review presents a recent data from the literature on the physiologic and pathophysiologic role of adipose tissue hormones (adiponectin, resistin, leptin). The article details the role of adipocytokines in atherogenesis. It also presents the results of studies depicting the relationship between subclinical hypothyroidism, lipid metabolism and insulin resistance as well as the impact of thyroid dysfunction upon the secretion of adipocytokines.